2001
DOI: 10.4049/jimmunol.166.11.6735
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid P Component Binds to Fcγ Receptors and Opsonizes Particles for Phagocytosis

Abstract: Serum amyloid P component (SAP) is a member of the pentraxin family of proteins. These proteins are characterized by cyclic pentameric structure, calcium-dependent ligand binding, and frequent regulation as acute-phase serum proteins. SAP is the serum precursor of the P component of amyloid. It binds to a broad group of molecules, including autoantigens, through a pattern recognition binding site. The related pentraxin, C-reactive protein (CRP), is a strong acute-phase reactant in man and an opsonin. We previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(158 citation statements)
references
References 38 publications
5
150
1
2
Order By: Relevance
“…Acute-phase reactant gene expression following LPS challenge was generally similar in ME7 and NBH animals, but PTX3 was highly induced by LPS in prion-diseased mice compared with control animals. PTX3 is a member of the pentraxins, which are thought to opsonize apoptotic cells, pathogens, and debris for phagocytosis by Fc␥ receptor-expressing cells (Bharadwaj et al, 2001;Mold et al, 2002a,b). Like C-reactive protein, PTX3 has been shown to exert control over the degree of activation of macrophages: PTX3 overexpressing macrophages produce more robust responses to LPS challenges than controls (Dias et al, 2001).…”
Section: Cns Consequences Of Systemic Inflammationmentioning
confidence: 99%
“…Acute-phase reactant gene expression following LPS challenge was generally similar in ME7 and NBH animals, but PTX3 was highly induced by LPS in prion-diseased mice compared with control animals. PTX3 is a member of the pentraxins, which are thought to opsonize apoptotic cells, pathogens, and debris for phagocytosis by Fc␥ receptor-expressing cells (Bharadwaj et al, 2001;Mold et al, 2002a,b). Like C-reactive protein, PTX3 has been shown to exert control over the degree of activation of macrophages: PTX3 overexpressing macrophages produce more robust responses to LPS challenges than controls (Dias et al, 2001).…”
Section: Cns Consequences Of Systemic Inflammationmentioning
confidence: 99%
“…Short-chain pentraxins are soluble pattern recognition receptors produced in the liver in response to inflammatory signals and subsequently act as multifunctional antibodies in the innate immune system (Ganapathi et al, 1991;Lu et al, 2012). PTXs also trigger the complement system via the classical complement pathway through C1q Volanakis and Kaplan, 1974) and increase pathogen clearance via phagocytosis (Bharadwaj et al, 2001). Short-chain pentraxins are involved in acute-phase response (APR) and recognise various pathogenic bacteria or cellular debris in a characteristic calcium-dependent manner (Abernethy and Avery, 1941;Thompson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Therefore, we hypothesized that the hSAP in plasmid-protein complexes might facilitate the adsorption and phagocytosis of DNA when hSAP binds its membrane receptors on monocytes. To test this hypothesis, we first confirmed the monocyte-binding ability of the hSAP-DNA complex using the human promonocytic cell line THP-1-cell line-derived macrophages (MDMs) as a cell model.…”
Section: Resultsmentioning
confidence: 99%
“…21 Most importantly, several reports have shown that SAP strongly binds to CD14 + monocytes 22 and opsonizes its ligands in an Fc receptor-dependent manner. [23][24][25][26] In this regard, hSAP has been considered a candidate DNA vaccine 'scavenger' that requires further investigation. In this study, we investigated the plasmid-binding and the DNA clearance activities of hSAP and the role of SAP in plasmid transfection in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%